Strategi Guru PAI dalam Menanamkan Karakter Disiplin Dan Tanggung Jawab Melalui Pembelajaran Berbasis Nilai Di SMK Muhammadiyah 02 Boja - Kurnia, Rifka; Hadi, Syaiful (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
Islamic Religious Education (PAI) has an important role in shaping the character of students, especially in terms of discipline and responsibility. This study aims to analyze the strategies used by PAI teachers in instilling these values through value-based learning. The research method used is qualitative with a case study approach in SMK Muhammadiyah 02 Boja. Data collection is carried out through observation and interviews. The results showed that the PAI teacher applied various strategies, such as exemplary, habituation, positive reinforcement, and reflection of values in learning activities. In addition, the integration of disciplinary values and responsibilities in teaching materials and experience-based learning activities is a key factor in the successful implementation of the character. Thus, value -based learning strategies can be an effective approach in shaping the character of students who are disciplined and responsible.